Understanding the acceptance of Malaysian societies towards journalists' news gathering practices in tragedy news reporting. - Loke, Elween Wei Jie (2011)
This study examined the acceptance of Malaysian societies towards crime or social beat journalists in their tragedy news gathering and reporting practices. A survey questionnaire was answered by 50 respondents who had interaction experience with crime or social beat journalists when tragedy happened, in which three were selected to undergo intensive interviews with the researcher. At the same time, three journalists from three newspapers of different languages who involve in tragedy news reporting were also being interviewed to obtain the conventional tragedy news reporting techniques in local context. A perceptual framework on sociological theories especially on attitude formation was constructed to pave a more comprehensive path that led to answering the various reasons behind perceptions such as professionalism, credibility and trustworthiness as well as attitude and level of tolerance that the public has on Malaysian tragedy news reporting journalists. The findings showed that despite the public has certain amount of respect towards the occupation of a journalist, they would not want to get involve with tragedy news reporting journalists as they see this as a disruption to their private lives when they are exposed in the media. The study also demonstrated that level of tolerance is not directly affected by education background of a person but it is implicitly cultivated based on other factors, in which privacy importance was one of the factors.